A study of fatigue among nurses in Hospital Universiti Sains Malaysia (HUSM) - Raseli, Farah Nafeesha Mohamed (Universiti Sains Malaysia, 2012)
This research was conducted to study on occupational fatigue experienced by nurses in Hospital Universiti Sains Malaysia (HUSM). The specific objective was to obtain the prevalence of occupational fatigue among nurses. This research also aimed to find the relationship between fatigue with employment data and also to determine the highest risk factor that cause fatigue. The respondents of the study were consisting of all nurses as a major group in healthcare services in Hospital Universiti Sains Malaysia (HUSM), Kelantan. 219 respondents have been selected randomly from ward, clinic and laboratory participated in this study. Questionnaires were used to collect field data and then analyze using Statistical Package for the Social Sciences (SPSS). From the analysis, it was found that prevalence of respondents having high fatigue is 56.4% while as for low fatigue is 43.6% and this showed that the prevalence of respondents having high fatigue is great. The result indicated the existence of correlations between working experience with fatigue represented p-value which is 0.043. Meanwhile, there is no association between work location and fatigue as the p-values are greater than 0.05. The result of this research also shows that no association between working in shift and fatigue. Last part of this study has determined five highest risk factors contributing fatigue which are; nurses shorthanded, work stress, excessive workload, improper sleep habits and high expectations/demands from patients and families.